2013
DOI: 10.14257/ijdrbc.2013.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Investigation of Abandoned GSIS Building in Manila

Abstract: a) Deterioration damage of concrete of the abandoned GSIS building is increasing as the years pass by; b) The abandoned GSIS building is still in serviceable condition in terms of its structural members; c) Steel corrosion and concrete deterioration are the major factors that affected the stability and integrity of structural members of the abandoned GSIS building in Manila; d) There is a difference between the design loads used in the GSIS building in Manila from the present design codes of National Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This increase in strength with respect to the concrete containing untreated rubber particles is thought to be attributed to the surface modification of the recycled particles. The saturated sodium hydroxide solution had an effect on the hydrophilic of the rubber allowing it to adhere better to the cement paste that surrounded it [16]. It is generally found that as the paste aggregate bond increases so does the strength of the concrete whether in tension, flexure or compression.…”
Section: Methodsmentioning
confidence: 99%
“…This increase in strength with respect to the concrete containing untreated rubber particles is thought to be attributed to the surface modification of the recycled particles. The saturated sodium hydroxide solution had an effect on the hydrophilic of the rubber allowing it to adhere better to the cement paste that surrounded it [16]. It is generally found that as the paste aggregate bond increases so does the strength of the concrete whether in tension, flexure or compression.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of excreta can vary in function of factors like the type of diet, the climate and lifestyle, but the proportion of nutrients and water excreted remains roughly the same independent of the total output [14,17,23]. Humans excrete on average sufficient amounts of nitrogen, phosphorous and potassium as plant nutrients to grow the 230 kg of crops they need annually [11,18]. Besides the nutrient content of the different partial flows, the distribution of pathogens is of high interest as well.…”
Section: Characteristics Of Human Excreta and Gray Watermentioning
confidence: 99%
“…Industrial furnaces are built of brick, which conduct heat so slowly that a high temperature within is barely apparent in the temperature of th e other surface. Steam pipes and water pipes are commonly insulated with thick wrappings of fiberglass pulp [10,12]. Since insulators prevent the flow of heat in either direction, refrigerators are commonly constructed with double walls separated by an air space (air being a poor conductor) and lined with some insulating material .The use of double walls or hollow tiles in buildings prevents the entrance of heat and its escape.…”
Section: Related Literaturementioning
confidence: 99%